2013
DOI: 10.1563/aaid-joi-d-10-00151
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Surface Treatments on Cement-Retained Implant-Supported Restorations

Abstract: The purpose of this study was to evaluate the effects of the various surface treatment methods on the retention of single crowns on implant abutments. The study included 50 single crowns that were cemented with adhesive resin cement onto the ITI solid abutments. The specimens were randomly divided into 5 groups, each including 10 specimens according to the following surface treatments: group C, control, abutments remained unaltered as control; group L, etching with CO(2) laser; group SB, sandblasting with 50-μ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
24
1
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 28 publications
1
24
1
5
Order By: Relevance
“…First of all, the results of present study confirmed that making roughened surface results in higher values of retentive strength as reported elsewhere (2,9,14,15,19,20).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…First of all, the results of present study confirmed that making roughened surface results in higher values of retentive strength as reported elsewhere (2,9,14,15,19,20).…”
Section: Discussionsupporting
confidence: 92%
“…There have been many studies about the effect of surface treatment on retention strengths of cemented prostheses to the abutments (4,5,9,11,14). However, few studies evaluated the effect of nano scale surface treating on retentive strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study higher shear bond strength values were obtained with group CSP and DSP than group S and group D respectively. Silane coupling with heat treatment may be effective on titanium surface to increase shear bond strength [20]. When compared traditional surface treatment methods, with this system more favorable results were obtained in adhesive prostheses, metal-composite fixed partial denture and crowns, telescopic crowns and removable partial dentures [12].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in the present study silicoating did not statistically affect the shear bond strength to titanium alloy. The Mohs hardness of titanium, silicon dioxide, aluminum oxide and synthetic diamond are 6, 6.5, 9 and 10, respectively [20]. Hardness of abrasive material did not affect the bond strength [18].…”
Section: Discussionmentioning
confidence: 99%